Perancangan Sistem Informasi Stok Darah Real time di Palang Merah Indonesia (PMI) Surakarta - Roni Zakaria; Muhammad Hisjam; Wicaksono Febriantoro (Performa: Media Ilmiah Teknik Industri, 2008)
At this time in PMI Surakarta, information system that connects the Hospital as blood consumer and PMI as blood supplier has not optimum yet, consequently, sometimes PMI has problem to serve demand from consumer because the blood is out of stock. Furthermore, response time from PMI Surakarta in serving the people and the usefulness of active voluntary donor has not optimum yet, these problems also influence PMI service quality. On the other hand, demand for blood can not be cancelled and have emergency character. Based on those problems, it is needed to design real time blood stock information system in PMI Surakarta. The aims of information system design is to increase the easiness and the quality system that is exist now in order to integrate PMI, blood consumer society and donor community. Thus blood stock position and blood demand can be known and be monitored along the time with media that people easy to access such as website and value added short message service (VASMS). The new system has ability to trace volunteer donor data, mobile unit, health of donor data, blood stock data, test result of serology and crossmatch data, can make real time quantity and blood genre report, can search at donor database quickly and also can give real time blood stock information via website in www.uns.ac.id/pmi and via VASM 3011 (only for Indosat costumer).